Formation of competitive advantages of machine-building enterprises on the basis of the benchmarking concept - Tkachova, N. P.; Kobielieva, T. O.; Pererva, P. G. (My University, 2021)
The article substantiates the theoretical bases, methodological recommendations and practical proposals for the formation and evaluation of competitive advantages of machine-building enterprises using the concept of benchmarking. Proposals for the management of competitive advantages in two inextricably linked ways: improvement in market activity of the company and the direct or relative decrease in the results of the use of the main competitive advantages of the market rivals of this company.
Keywords: benchmarking; principles; varieties; competitive advantages; industrial enterprises